IS THIS ¿MUSIC? EXPERIMENTAL SOUND BASED ON THE APPROPRIATION OF NEW TECHNOLOGIES (Orfeu, 2017)
This paper presents a reflection onsound experimentation and possible paradoxes between music, sound and languagein contemporary artistic production, fromthe appropriation of new digital technologies. From the moment that an acousticinstrument is connected to an interfacecapable of processing its signal, we haveaccess to the intrinsic potentialities of thesound. Combining investigative processesthat can perform the exchange of data and/or signals between the acoustic instruments, electronic devices/circuits, mobilecomputers, controllers, smartphones, wireless communication networks, sensors,amplified objects, etc., experimentationwith mobile digital devices has opened upan irreversible rift in sound making, greatlyexpanding artistic possibilities. Sound experimentation, its creation and diffusionare increasingly close to the skin, touch,and are increasingly close to the humanbody itself. By expanding the focus beyondthe traditional approaches on rhythm, melody and harmony, which are linked to acertain period of Western music, and engaging on enhanced and deep listeningexperiences, we realize the potential thatsound carries, with all its expressive nuances. Thus, the appropriation of new technologies enables the creation of a specifictype of performance and composition anchored in sound manipulation and a moredetailed listening experience that may bedissociated from a specific referentiality.
Keywords: Research of contemporary musical sound; new technologies in music; sound experimentation; musical improvisation